HDL: Fact, fiction, or function? HDL cholesterol and cardiovascular risk. (13th May 2019) - Allard-Ratick, Marc P; Kindya, Bryan R; Khambhati, Jay; Engels, Marc C; Sandesara, Pratik B; Rosenson, Robert S; Sperling, Laurence S
Abstract: The measurement of high-density lipoprotein cholesterol is highly utilized by clinicians to help predict cardiovascular risk, but this measure is not causally associated with atherosclerotic cardiovascular disease events. The use of Mendelian randomization studies has led to a change in investigative attention from the high-density lipoprotein cholesterol concentration to its physiological functions. High-density lipoprotein plays key roles in important pathways related to the development of atherosclerotic disease including reverse cholesterol transport, oxidation and inflammation, and endothelial function as well as in other physiological systems including immune system modulation, cellular apoptosis, and endothelial progenitor cell homeostasis. The identification of dysfunctional high-density lipoprotein may better predict future cardiovascular events compared to numerical high-density lipoprotein cholesterol and aid in enhanced clinical risk stratification. The emergence of discrete physiological measurements of high-density lipoprotein, such as cholesterol efflux capacity and the high-density lipoprotein inflammatory index, may provide an opportunity for clinical application in the future. However, the validity of these measurements and their commercial availability remain barriers to a realistic transition to clinical medicine.